Two-level model of decision-making in case of dependence of criteria weights on conditions of environment - Селякова, Светлана Михайловна (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
The case of a multicriteria problem of decision-making in the conditions of definiteness in case of dependence of estimates of importance of the fuzzy description criteria on the environment conditions is considered. The two-level model of decision-making allowing at the bottom level to define of weight of criteria is offered, and on the top – to solve a problem of a choice of the best alternative.